Identification results for inverse source problems in unsteady Stokes flows. (6th January 2015) - Martins, Nuno F M
Abstract: We establish identification results in an inverse source problem for the two-dimensional Brinkman equations. This identification problem is cast in the context of a nondestructive evaluation problem that consists in retrieving a pair of forces, namely a body force and a divergence force, from the corresponding Cauchy data. Results are established for data obtained from a single measurement and from several measurements. Extension to three-dimensional problems is also discussed.